AUT DEDERE AUT JUDICARE: CONSTITUTIONAL PROHIBITIONS ON EXTRADITION AND THE STATUTE OF ROME - Rabbat, Paul (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2002)
In many States, the ratification of the Rome Statute of the International Criminal Court raises the issue of the statute’s compatibility with certain dispositions of the national constitution. The potential issues of constitutional incompatibility are generally within one of the following categories: prohibitions on extradition, constitutional immunities from criminal prosecution, prohibitions on life imprisonment and concerns as to due process. The scope of this paper is limited to the first of these issues. The ICC will not prosecute individuals in absentia and will rely heavily on State cooperation to gain physical custody of suspects. In the author’s view, this reality renders the removal of impediments to prosecution all the more essential.The prohibition on extradition sits at the extreme end of a spectrum of provisions relative to mobility rights afforded to citizens within a great number of national constitutions. These dispositions vary in intensity. While some simply assert the citizens’ right to move about the national territory and to enter or leave it freely, others aim explicitly at shielding citizens from prosecution in external jurisdictions. After examining the respective ways in which States have addressed potential impediments to the surrender of individuals to the ICC, the author makes a case for constitutional amendment in order to ensure full compliance.